Non-Tax Revenue Mechanism for Fishing Vessels at the Jepara Public Wharf - Hariyanti Retno; Priadi Antoni; Kristini Florentina; Sari Dewi Kartika; Ridwan Achmad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study analyzes the mechanism of Non-Tax State Revenue (PNBP) collection from fishing vessels using the public wharf at Jepara Port and formulates a governance model that balances legality, fiscal effectiveness, and the protection of small-scale fishermen. An embedded single-case study design combines socio-legal analysis, process mapping, semi-structured interview transcripts and observations, and a framework matrix across the dimensions of jurisdiction, tariff classification, collection workflow, data integration, and equity. The results indicate that tariff imposition is determined by the authority of the facility manager and the services utilized, rather than by vessel type alone. Collection proceeds through arrival registration, gross tonnage verification, e-billing, payment, and digital verification, supported by coordination between the Port Operations Unit and the Fisheries Harbor Master. Regulatory overlaps, informal tariff analogies, data fragmentation, limited public outreach, and affordability risks nevertheless persist. The novelty of this research lies in a facility-jurisdiction-proportionality model that requires explicit tariff classification, an integrated registry, an audit trail, limited coordination of authority, a relief pathway, and periodic evaluation.